Melatonin in Plants - Haitao Shi (Frontiers Research Topics, 2017)
This topic focuses on distribution, synthesis, metabolism, and the in vivo roles of melatonin in plants, with 1 editorial, 3 reviews, 21 original research studies and 1 corrigendum.